Gold nanoparticles decorated with ovalbumin-derived epitopes: effect of shape and size on T-cell immune responses. Issue 31 (7th July 2022) - Egorova, Elena A.; Lamers, Gerda E. M.; Monikh, Fazel Abdolahpur; Boyle, Aimee L.; Slütter, Bram; Kros, Alexander
Abstract : Gold nanoparticles (GNPs) can be manufactured in various shapes, and their size is programmable, which permits the study of the effects imposed by these parameters on biological processes. Abstract : Gold nanoparticles (GNPs) can be manufactured in various shapes, and their size is programmable, which permits the study of the effects imposed by these parameters on biological processes. However, there is currently no clear evidence that a certain shape or size is beneficial. To address this issue, we have utilised GNPs and gold nanorods (GNRs) functionalised with model epitopes derived from chicken ovalbumin (OVA257–264 and OVA323–339 ). By using two distinct epitopes, it was possible to draw conclusions regarding the impact of nanoparticle shape and size on different aspects of the immune response. Our findings indicate that the peptide amphiphile-coated GNPs and GNRs are a safe and versatile epitope-presenting system. Smaller GNPs (∼15 nm in diameter) induce significantly less intense T-cell responses. Furthermore, effective antigen presentation via MHC-I was observed for larger spherical particles (∼40 nm in diameter), and to a lesser extent for rod-like particles (40 by 15 nm). At the same time, antigen presentation via MHC-II strongly correlated with the cellular uptake, with smaller GNPs being the least efficient. We believe these findings will have implications for vaccine development, and lead to a better understanding of cellular uptake and antigen egress from lysosomes into the cytosol.